THE IMPLEMENTATION OF THE FLYSWATTER GAME IN IMPROVING THE SEVENTH-YEAR STUDENTS’ VOCABULARY - Lubis, Rica Umrina; Hasibuan, Sri Wahyuni; Aisyah, Siti (Journal of English Education and Linguistics, 2024)
The purpose of this study is to determine whether teaching vocabulary using the Flyswatter game enhanced student vocabulary. The author used a flyswatter game as part of her action research in the classroom to find a solution. One cycle was used by the author in this study. Every cycle has four meetings. One class of twenty-four students participated in this investigation. The writer employed documentation, test sheets, and observation sheets as tools for gathering data. Based on the research findings, the students' progressive mean was displayed. The mean of the first meeting was 53.5; the second was 55.3; the third was 61.9; the fourth was 66.1 and the fifth was 75,5. As a result, the post-test mean was greater than the pre-test mean. The information collected from the observation sheet suggested that the pupils made progress. Research suggests that using the flyswatter game helps students' vocabularies. Finally, the flyswatter game may help SMPN 2 Tambangan students become more proficient in the language.